Rhizospheric bacillus spp. exhibit miticidal efficacy against oligonychus coffeae (Acari: Tetranychidae) of tea - Bora, Popy; Gogoi, Sukanya; Deshpande, Mukund Vinayak; Garg, Pankaj; Bhuyan, Rana P.; Altaf, Nilofar; Saha, Nikita; Borah, Sapna Mayuri; Phukon, Mousumi; Tanti, Nabajit; Saikia, Bishal; Ahmed, Shenaz Sultana; et al. (Microorganisms, 2023)
Oligonychus coffeae (Acari: Tetranychidae), popularly known as red spider mite (RSM) is one of the major pests of commercial tea (Camellia sinensis (L.) O. Kuntze) plantation world over. Many attempts have been made in the past to control this devastating pest using a variety of microbial bioagents, however, area-wise field success is very limited. We carried out an in vitro study to explore the potential of rhizospheric Bacillus spp. (B. amyloliquefaciens BAC1, B. subtilis LB22, and B. velezensis AB22) against O. coffeae through adulticidal and ovicidal activity. The 100% adult and egg mortality was observed with bacterial suspension (1 x 10(9 )CFU/mL) by B. velezensis AB22, showing the lowest LC50 values for both adults and eggs of O. coffeae, i.e., 0.28 x 10(5) and 0.29 x 10(5), respectively. The study also throws some insights into the underlying mechanism through electron microscopy study and identification of some putative pesticidal metabolites from all the species. The three Bacillus species were observed to have four commonly secreted putative bioactive secondary metabolites, brevianamide A, heptadecanoic acid, thiolutin, and versimide responsible for their bio-efficacy against O. coffeae. The outcome of our study provides a strong possibility of introducing Bacillus spp. as a biological miticide and developing synthetic metabolites mimicking the mechanistic pathway involved in microbial bioefficacy.
Keywords: Bacillus spp.; Biocontrol; organic tea; Secondary metabolites